Posttraumatic deformities of the bones, forming knee joint: general evaluation and treatment tactics - Romanenko, Konstantin (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
The aim of paper: to provide modern approach to diagnostics and treatment of deformities localized around knee joint and developed after distal metadiaphysis of femur and proximal metadiaphysis of tibia fractures. It was shown, that formed deformities provoke development of secondary adaptive changes in articular surfaces of knee and its stabilizers, thigh and shin muscles. It also impairs walking. The planning of treatment should be based on proper investigation: radiologic assessment of malaligned extremity and its computer tomography, ultrasound investigation of tendons and muscles, that provide function of knee joint, assess anatomic-functional characteristics of knee joint itself (range of motion, stability, osteoarthritic changes) and malfunction of whole extremity with malaligned segment, including walking ability. Standardized technique of roentgenographic investigation and standard parameters for proper image analysis are provided. The necessity to take into consideration all changes of impaired extremity and segment, but not only the results of roentgenograms assessment, for the working-out of treatment is emphasized. The main treatment goals are: restoration of weight-bearing ability, anatomic or almost anatomic realignment to restore three-dimension orientation of articular surfaces, improvement of walking function. The main types of treatment are: different osteotomies followed with fragments fixation using extrafocal or buried osteosynthesis (intramedullary nailing or plating), restoration of ligamentous structures, arthroplasty or arthrodesis. Main indications for every variant of surgical intervention are listed.